2008
DOI: 10.1016/j.jeconom.2008.09.035
|View full text |Cite
|
Sign up to set email alerts
|

Econometric estimation in long-range dependent volatility models: Theory and practice

Abstract: It is commonly accepted that some financial data may exhibit long-range dependence, while other financial data exhibit intermediate-range dependence or short-range dependence. These behaviours may be fitted to a continuous-time fractional stochastic model.The estimation procedure proposed in this paper is based on a continuous-time version of the Gauss-Whittle objective function to find the parameter estimates that minimize the discrepancy between the spectral density and the data periodogram. As a special cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 42 publications
1
28
0
Order By: Relevance
“…Continuous versions of Whittle estimation procedure have been considered, for example, in Anh et al [3,4], Avram et al [5], Casas and Gao [9], Gao [14], Gao et al [15,16], Leonenko and Sakhno [26].…”
Section: The Approach and Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Continuous versions of Whittle estimation procedure have been considered, for example, in Anh et al [3,4], Avram et al [5], Casas and Gao [9], Gao [14], Gao et al [15,16], Leonenko and Sakhno [26].…”
Section: The Approach and Resultsmentioning
confidence: 99%
“…It can be shown that the standard Taylor expansion methods based on the smoothed periodogram convergence results of type (3.4) and (3.5) with a general smoothing function g(λ; θ) and with the contaminated periodogram I T,X (λ) instead of I T,Y (λ), lead consistent and asymptotically normally distributed estimators of θ. We will not pursue this matter here (the details will be reported elsewhere), however, notice that in the special case of Whittle procedure, where g(λ; θ) = ∂ ∂ 1 f (λ,θ) · w(λ) the results of Anh et al [3], Avram et al [5], Casas and Gao [9], Gao [14], Gao et al [15,16], Leonenko and Sakhno [26] concerning consistency and asymptotic normality of the Whittle minimum contrast estimators constructed on the basis of the periodogram I T,Y (λ), continue to hold without change for estimators calculated on the basis of the contaminated periodogram I T,X (λ), under appropriate assumptions imposed on the model Y (t) on the smoothing function g(λ, θ) and on the trend M (t).…”
Section: The Approach and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some considered jumps in the dynamics of asset prices Andersen and Bollerslev (1997)]. Recent works on this problem can be found in [Casas and Gao (2008); Hu (2004)]. Most of these works assumed the model to be generated by the finite parameter model.…”
Section: Introductionmentioning
confidence: 99%